The Relationship between Community Knowledge and Attitudes towards Lepra Stigma in the Working Area of Malawei Public Health Center, Sorong City - Fitriani, Fitriani; Wahyuning Tyas, Lusia; Lia Afianti Loukaky (Fakultas Kedokteran, Universitas Mulawarman, 2024)
Background: Lepra creates a significant stigma within society, leading to the social rejection of people with lepra, which often results in discrimination. According to the Ministry of Health of the Republic of Indonesia in 2022, West Papua is the province with the highest incidence of Lepra in Indonesia, with a rate of 9.89 per 10,000 population. The aim of this study is to investigate the relationship between community knowledge and attitudes with the stigma surrounding Lepra in the working area of Malawei Public Health Center, Sorong City. Method: This research is a quantitative study with a cross-sectional design. The statistical test used was the Chi-square test. The research instrument was a questionnaire. The study was conducted in the working area of Malawei Public Health Center in Sorong City, specifically in RT 3/RW 4. The population in this study consists of 90 residents from RT 3/RW 4, with a sample size of 74 respondents calculated using the Slovin formula. Results: The study found a significant relationship between knowledge and the stigma of Lepra with a p-value of 0.000 < (α = 0.05). Additionally, there was a significant relationship between attitudes and the stigma of Lepra with a p-value of 0.000 < (α = 0.05). Conclusion: There is a relationship between community knowledge and attitudes with the stigma surrounding Lepra in the working area of Malawei Public Health Center, Sorong City